HUBUNGAN KECERDASAN EMOSIONAL, MEKANISME KOPING, DAN POLA ASUH TERHADAP DEPRESI PADA SISWA SMA NEGERI X DI WILAYAH LOMBOK BARAT - AMARANTA ERVANI RAHADI; YOLLY DAHLIA; WENDY HANDAYANI; SULATUN HIDAYATI (Universitas Mahasaraswati K. Mataram, 2024)
Adolescence is an important transition period for a person's development, and factors such as emotional intelligence, coping mechanisms, and parenting can influence the incidence of depression in adolescents. The study was based on data showing the high prevalence of depression in adolescents. This study aims to determine the relationship between emotional intelligence, coping mechanisms, and parenting patterns with depression in SMA Negeri X students in West Lombok Region. The results showed that there was a significant relationship between emotional intelligence, coping mechanisms, and parenting patterns with depression in SMA Negeri X students in the West Lombok Region with a p-value of <0.05 each.